School Learning Action Cell: Examining Links of a Lesson Study with Work Performance of Teachers - Herchel F Gumban; Maria Theresa P Pelones (ASEAN Multidisciplinary Research Journal, 2021)
Teacher quality can develop holistic learners who are value-driven, qualified with 21st century skills, and capable of driving the country toward the development and progress. The study aimed to find out how the activities of School Based Learning Action Cell (SLAC) as a lesson study program in the Philippines relates to Teacher’s Work Performance. The study applied quantitative and qualitative design and involved 11 selected public elementary schools located in the district of Norala in the province of South Cotabato. There were 129 randomly selected teachers and 6 key informants who participated in the study. Adapted questionnaires and group discussion guide questions were utilized for data gathering. Findings of the study showed that teachers were highly involved in SLAC activities to ensure professional growth, quality teaching, collaboration and problem-solving, and school development programs. The performance of teachers at work had also been found to be very satisfactory in all its indicators: content knowledge and pedagogy, learning environment and leaner diversity, curriculum and planning, and assessment and reporting. Based on simple linear regression, the data showed that when teachers participate in SLAC activities, their work performance increases. Implications for the professional development of teachers are given in the study.